The efficacy of manual therapy for chronic obstructive pulmonary disease: A systematic review. - Ji-Ae Roh (Public Library of Science (PLoS), 2021)
Background Manual therapy (MT) can be beneficial in the management of chronic obstructive pulmonary disease (COPD). However, evidence of the efficacy of MT for COPD is not clear. Therefore, we aimed to review the effects of MT, including Chuna, in people diagnosed with COPD. Methods MEDLINE via PubMed, EMBASE, The Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Database (CNKI), KoreaMed, Korean Medical Database (KMbase), and Oriental Medicine Advanced Searching Integrated System (OASIS) were searched. Randomized controlled trials (RCTs) and crossover RCTs were included. The main inclusion criteria were COPD diagnosis (forced expiratory volume in the first second [FEV1]/forced vital capacity [FVC] < 0.70). The primary outcomes were lung function and exercise capacity. The secondary outcomes were symptoms, quality of life (QoL), and adverse event (AE)s. Studies reporting one or both of the primary outcomes were included. The Cochrane RoB 2.0 tool was used to assess the risk of bias. Data synthesis and analysis were conducted according to the trial design. Results Of the 2564 searched articles, 13 studies were included. For the primary outcomes, the effect of MT on pulmonary function and exercise capacity in COPD was partly significant but could not be confirmed due to the limited number of studies included in the subgroups. For the secondary outcomes, no definitive evidence regarding the improvement of symptoms and QoL was found, and some minor adverse effects were reported. Conclusions There is insufficient evidence to support the role of MT in the management of COPD. High-quality studies are needed to thoroughly evaluate the effect of MT on COPD.